2017
DOI: 10.1159/000477253
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlates and Prognostic Significance of IL-8, sIL-2R, and Immunoglobulin-Free Light Chain Levels in Patients with Myelofibrosis

Abstract: Background: Chronic myeloproliferative neoplasms are characterized by clonal hematopoiesis and persistent inflammatory reaction. In this study, the clinical significance and prognostic impact of several inflammatory markers were evaluated in patients with BCR/ABL-negative myeloproliferative malignancies. Methods: Serum levels of interleukin-8 (IL-8) and lymphoid-associated activation markers - soluble interleukin-2 receptor (sIL-2R) and immunoglobulin-free light chains (FLC) - were evaluated in patients with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…Studies by Tefferi and colleagues revealed elevated serum levels of IL-1β in PV (n = 65) and PMF (n = 127) patient cohorts [ 21 , 28 ]. Furthermore, elevated levels of IL-12, IL-15, IP-10, IL-8, IL-2, and s-IL-2R in PMF patients have been correlated with decreased/poor overall survival [ 21 , 28 , 57 ]. Other very important participating factors, the NLRP3 and AIM2 inflammasomes, have appeared as crucial players in regulating certain hematological pathologies, e.g., myelodysplastic syndrome (MDS), MPNs, cardiovascular risk, and leukemia [ 58 , 59 ].…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%
“…Studies by Tefferi and colleagues revealed elevated serum levels of IL-1β in PV (n = 65) and PMF (n = 127) patient cohorts [ 21 , 28 ]. Furthermore, elevated levels of IL-12, IL-15, IP-10, IL-8, IL-2, and s-IL-2R in PMF patients have been correlated with decreased/poor overall survival [ 21 , 28 , 57 ]. Other very important participating factors, the NLRP3 and AIM2 inflammasomes, have appeared as crucial players in regulating certain hematological pathologies, e.g., myelodysplastic syndrome (MDS), MPNs, cardiovascular risk, and leukemia [ 58 , 59 ].…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%
“…In other studies on MF subjects, the correlation of specific cytokines with lower survival (IL2R, IL8), transfusion dependence (IL2R, IL8), higher number of leukocytes (IL2R), circulating blasts (IL-8), lower platelet count (IP10), and JAK2V617F positivity (IL2R) was demonstrated [44]. All of these findings represent factors independent from those used in the clinical Dynamic International Prognostic Scoring System (DIPSS).…”
Section: Rantesmentioning
confidence: 76%
“…Previous studies have identified that the serum (and/or plasma) of patients with MF contains greater levels of several proinflammatory cytokines than that of nondiseased individuals. More specifically, the plasma of these patients contains greater levels of TGF-β, both as total and activated form [ 7 ], and interleukin-8 (IL-8), and the plasma levels of IL-8 were found to predict the severity of the symptoms and progression to leukemic transformation [ 8 , 9 ]. Both TGF-β and IL-8 are abnormally produced at high levels by the megakaryocytes present in the bone marrow of myelofibrosis patients [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%